2021
DOI: 10.3390/jcm10091997
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Pre-Frailty Risk Assessment during Shelter-In-Place Measures Based on Multimodal Biomarkers Collected from Smart Telemedical Wearables

Abstract: Wearable devices play a growing role in healthcare applications and disease prevention. We conducted a retrospective study to assess cardiovascular and pre-frailty risk during the Covid-19 shelter-in-place measures on human activity patterns based on multimodal biomarkers collected from smartwatch sensors. For methodology validation we enrolled five adult participants (age range: 32 to 84 years; mean 57 ± 22.38; BMI: 27.80 ± 2.95 kg/m2) categorized by age who were smartwatch users and self-isolating at home du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A small retrospective observational study in Poland showed similar results [22]. Five subjects who self-isolated at home during the COVID-19 pandemic were enrolled in this study, and their daily steps, resting heart rate, and sleep duration were recorded for 464 days.…”
Section: Physical Activity During the Covid-19 Pandemicmentioning
confidence: 55%
“…A small retrospective observational study in Poland showed similar results [22]. Five subjects who self-isolated at home during the COVID-19 pandemic were enrolled in this study, and their daily steps, resting heart rate, and sleep duration were recorded for 464 days.…”
Section: Physical Activity During the Covid-19 Pandemicmentioning
confidence: 55%
“…specialized care. So, it could monitor sleep quality and provide feedback on how to improve sleep habits, which may help reduce the risk of frailty [ 32 ]. Additionally, researchers and practitioners can use motion sensors mounted on the upper limbs (i.e., lower arm/wrist, upper arm) to evaluate dietary intake and eating behavior in both laboratory and free-living conditions by using wearable sensing technology (e.g., commercial inertial sensors, fitness bands, and smart watches) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent consensus on frailty screening in primary care settings supports individual-level and opportunistic screening at point-of-care [50]; however, participants in that study noted that at present there is little evidence for the effectiveness of population-level screening, monitoring and surveillance of pre-frailty [58]. Considering recent events such as the COVID-19 pandemic and advancements in healthcare technology, innovative solutions including walking sensors [59], remote patient monitoring and telehealth [60] may represent the future of resourceefficient rapid screening for pre-frailty. Given their novelty, these new and potentially practical Author accepted version prior to publisher formatting.…”
Section: Screening and Assessmentmentioning
confidence: 99%